Breaking bad news: doctors’ skills in communicating with patients - Silveira, Francisco José Ferreira da; Botelho, Camila Carvalho; Valadão, Carolina Cirino (São Paulo Medical Journal, 2017)
CONTEXT AND OBJECTIVE: Breaking bad news is one of doctors’ duties and it requires them to have some skills, given that this situation is difficult and distressful for patients and their families. Moreover, it is also an uncomfortable condition for doctors. The aim of this study was to evaluate doctors’ capacity to break bad news, ascertain which specialties are best prepared for doing this and assess the importance of including this topic within undergraduate courses. DESIGN AND SETTING: Observational cross-sectional quantitative study conducted at a university hospital in Belo Horizonte (MG), Brazil. METHODS: This study used a questionnaire based on the SPIKES protocol, which was answered by 121 doctors at this university hospital. This questionnaire investigated their attitudes, posture, behavior and fears relating to breaking bad news. RESULTS: The majority of the doctors did not have problems regarding the concept of bad news. Nevertheless, their abilities diverged depending on the stage of the protocol and on their specialty and length of time since graduation. Generally, doctors who had graduated more than ten years before this survey felt more comfortable and confident, and thus transmitted the bad news in a better conducted manner. CONCLUSION: Much needs to be improved regarding this technique. Therefore, inclusion of this topic in undergraduate courses is necessary and proposals should be put forward and verified.